+0  
 
-1
275
1
avatar

(2-i)(2/5 + 1/5i)

Guest Apr 26, 2017
 #1
avatar+88899 
+2

(2 - i)(2/5 + 1/5i) =     factor 1/5 from the second term

 

(1/5) (2 - i)  (2 + i)  =

 

(1/5)  (4  - i^2)  =

 

(1/5)  (  4 -  -1)  =

 

(1/5) (5)   =  

 

1

 

 

cool cool cool

CPhill  Apr 26, 2017

16 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.